A high-performance base film for composite current collector and preparation method thereof

By mixing PP masterbatch with composite modified auxiliary particles and performing a multi-step preparation process, the problems of poor copper adhesion, insufficient flame retardant performance and tensile strength of the PP base film in the composite current collector are solved, and a high-performance base film is achieved. Membrane preparation and application.

CN118721807BActive Publication Date: 2025-01-21扬州博恒新能源材料科技有限公司

Patent Information

Application Number
CN202410751486.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-12
Publication Date
2025-01-21
Estimated Expiration
2044-06-12

AI Technical Summary

Technical Problem

The existing PP base film has poor copper adhesion ability, insufficient flame retardant performance and tensile strength in composite fluid collection, which limits its application in composite fluid collection base film.

Method used

By mixing PP masterbatch with composite modified auxiliary particles, melt extrusion, biaxial stretching, heat setting and surface corona treatment are performed to prepare a high-performance base film with improved copper adhesion, flame retardant properties and tensile strength. .

Benefits of technology

It significantly improves the copper adhesion ability, flame retardant performance and tensile strength of the PP base film, and promotes the large-scale application of PP materials in composite current collector base films.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004888112380000161
    Figure BDA0004888112380000161
  • Figure BDA0004888112380000171
    Figure BDA0004888112380000171
Patent Text Reader

Abstract

The present invention discloses a high-performance base film for composite current collector and a preparation method thereof, the method comprising the following steps: S1, mixing PP masterbatch with composite modified auxiliary particles, melt extruding, cooling to obtain a cast sheet; S2, preheating the cast sheet and biaxially stretching it to obtain a stretched sheet; S3, heat setting, cooling, and obtaining a rough product; S4, performing surface corona treatment on the rough product; S5, winding, aging treatment, and slitting to obtain a high-performance base film for composite current collector. The present invention can well solve the problem of poor copper adhesion of conventional PP base films, and can also significantly improve the flame retardant properties and tensile strength of the PP base film, which is conducive to promoting the large-scale application of PP materials in composite current collector base films.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of composite current collector base film materials, and in particular to a high-performance base film for a composite current collector and a preparation method thereof. Background Art

[0002] The current collector is a general term for copper foil and aluminum foil in lithium batteries, which carry active materials and collect current. Composite current collectors are made by depositing copper / aluminum atoms on the surface of polymer-based films to form composite copper foil current collectors or composite aluminum foil current collectors. Compared with traditional current collectors (aluminum foil or copper foil), they can reduce the amount of metal used, improve energy density and safety, and have been widely used. The mainstream polymer-based films currently used include PET and PP films.

[0003] The composite current collector adopts a "sandwich" structure, which is "metal-PET / PP-metal", that is, a base film (PET or PP film) in the middle. For example, the copper-plated composite current collector usually has a layer of copper of about 1 μm on the upper and lower sides of the base film to form a composite structure.

[0004] PP and PET are the conventional materials for composite current collector base film. PET base film has the following advantages: 1) PET base film has greater mechanical tensile strength, good tensile properties, and relatively less difficulty in metallization process; 2) Stronger interface bonding force. PET film is a polar polymer and has stronger copper adhesion ability. However, PET base film has the following defects: chemical stability is worse than PP. PET contains ester groups and will decompose under the action of strong acid, strong alkali or water vapor.

[0005] PP has the following advantages: 1) Strong acid resistance: PP molecules do not contain ester bonds and are not easily corroded by strong acids, so they have better resistance to strong acids. PP has excellent chemical stability and is inert to most acids, alkalis, salts, and oxidants. At room temperature, the number of cycles of PET and PP composite foils can remain consistent. However, under high temperature conditions, the number of cycles of PP composite foils performs better than that of PET composite foils. 2) Better ductility: PP has better ductility and a higher elongation at break than PET. 3) PP film is lighter and has a lower density (potential for large cost reduction). The density of PET can range from 1.2 to 1.38 g / cm 3 , the density of PP is about 0.89 to 0.91 g / cm 3 The main defects of PP-based film are: general adhesion, PP film is a non-polar polymer, compared with PET, its copper adhesion ability is poor; on the other hand, its flame retardancy is poor, and the limiting oxygen index is generally 17-18.5%.

[0006] Therefore, PP has great potential for application as a composite current collector base film, but the above-mentioned defects need to be properly addressed. Summary of the invention

[0007] The technical problem to be solved by the present invention is to provide a high-performance base film for a composite current collector and a preparation method thereof in view of the deficiencies in the above-mentioned prior art.

[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is: a method for preparing a high-performance base film for a composite current collector, comprising the following steps:

[0009] S1, mixing the PP masterbatch with the composite modified auxiliary particles, melt-extruding, and cooling to obtain a cast sheet;

[0010] S2, preheating the cast sheet and then biaxially stretching it to obtain a stretched sheet;

[0011] S3, heat setting, cooling, and obtaining a crude product;

[0012] S4. Performing surface corona treatment on the crude product;

[0013] S5, winding, aging treatment, slitting, and obtaining a high-performance base film for a composite current collector.

[0014] Preferably, the composite modified auxiliary particles are prepared by the following method:

[0015] 1) Modifying wollastonite with stearic acid to prepare modified wollastonite;

[0016] 2) using stearic acid and a silane coupling agent to perform composite modification on magnesium hydroxide to prepare modified magnesium hydroxide;

[0017] 3) Preparation of maleic anhydride grafted polypropylene: PP-MAH;

[0018] 4) PP-MAH, modified wollastonite and modified magnesium hydroxide are blended and extruded by a twin-screw extruder to obtain an auxiliary particle precursor;

[0019] 5) Grafting acrylonitrile onto the PP of the auxiliary particle precursor, and then performing an amination treatment to obtain the composite modified auxiliary particle.

[0020] Preferably, step 1) is specifically:

[0021] 1-1) adding 50-200 mg of wollastonite into 100-300 mL of anhydrous ethanol, and ultrasonically dispersing for 10-45 min to obtain a wollastonite dispersion;

[0022] 1-2) 1.25-5 mg of stearic acid is dissolved in 10-40 mL of ethanol, stirred for 2-15 min, the resulting mixture is added to the wollastonite dispersion, stirred for 5-30 min, then heated to 75-85 ° C, stirred at 500-1000 rpm for 30-90 min, cooled to room temperature, filtered, and the solid product is dried at 60-75 ° C for 8-16 h to obtain modified wollastonite.

[0023] Preferably, step 2) is specifically:

[0024] 2-1) adding 50-200 mg of magnesium hydroxide to 100-400 mL of anhydrous ethanol, and ultrasonically dispersing for 15-60 min to obtain a magnesium hydroxide dispersion;

[0025] 2-2) 0.75-3 mg of stearic acid and 0.65-2.5 mg of silane coupling agent KH-570 are added to 15-60 mL of ethanol, stirred for 5-30 min, and the resulting mixture is added to a magnesium hydroxide dispersion, ultrasonically dispersed for 15-60 min, then heated to 70-80 ° C, stirred at 300-800 rpm for 60-120 min, cooled to room temperature, filtered, and the solid product was dried at 60-70 ° C for 5-20 h to obtain modified magnesium hydroxide.

[0026] Preferably, step 3) is specifically:

[0027] The PP is dried at 70-85°C for 15-60 minutes, then mixed with MAH, DCP, and TPP, stirred for 5-30 minutes, and then banburyed at 160-185°C for 5-20 minutes under continuous stirring, and cooled to room temperature to obtain maleic anhydride grafted polypropylene: PP-MAH;

[0028] Among them, the mass ratio of PP:MAH:DCP:TPP is 100:2.25-6.5:0.35-1.4:0.15-0.7.

[0029] Preferably, step 4) is specifically:

[0030] PP-MAH, modified wollastonite and modified magnesium hydroxide are mixed, stirred at 90-105°C for 15-60 minutes, then added into a twin-screw extruder, extruded and granulated at 175-190°C to obtain an auxiliary granule precursor;

[0031] Wherein, the mass ratio of PP-MAH: modified wollastonite: modified magnesium hydroxide is 100: 4-16: 2.5-10.

[0032] Preferably, step 5) is specifically:

[0033] 5-1) Soak the auxiliary particle precursor in acetone for 4-12 hours, then rinse with deionized water, and dry at 50-70°C for 3-12 hours;

[0034] 5-2) Add acrylonitrile to N, N-dimethylacetamide solution to prepare a grafting monomer solution with a mass fraction of acrylonitrile of 10-20%; then add the auxiliary particle precursor to the grafting monomer solution at a mass ratio of acrylonitrile to auxiliary particle precursor of 1.3-2.4:1, seal and ultrasonically oscillate for 1.5-6 hours, then irradiate, control the irradiation dose to 30-100KGy, filter after irradiation, soak the solid product with DMF for 0.5-2 hours, filter, wash the solid with ethanol, and then dry at 60-75°C for 3-12 hours to obtain grafted modified auxiliary particles;

[0035] 5-2) adding the grafted modified auxiliary particles, DETA and aluminum chloride into acetone and stirring evenly, reacting at 100-120° C. for 1.5-6 hours, cooling to room temperature after the reaction, filtering, washing the solid product with deionized water and ethanol in sequence, and then vacuum drying at 65-80° C. for 5-24 hours to obtain composite modified auxiliary particles;

[0036] Wherein, the mass ratio of graft modified auxiliary particles: DETA: aluminum chloride is 100: 11.5-36: 0.5-2. Preferably, the method for preparing the high-performance base film for the composite current collector comprises the following steps:

[0037] S1. Mix the PP masterbatch and the composite modified auxiliary particles in a mass ratio of 100:5-23, stir for 15-60 minutes, and then heat to 200-240° C. through a screw melt extrusion system to form a molten body, inject into a die head for extrusion after filtering, and cool to obtain a cast sheet;

[0038] S2, preheating the cast sheet to 100-120°C, and biaxially stretching it at 150-175°C, with a longitudinal stretching ratio of 2-3.8 times and a transverse stretching ratio of 2.3-4 times to obtain a stretched sheet;

[0039] S3, heat setting the stretched sheet at 160-180° C. for 10-20 seconds, and then cooling to room temperature to obtain a crude product;

[0040] S4. Performing surface corona treatment on the crude product;

[0041] S5, winding, aging treatment: standing at 25-38°C for 1-3 days; cutting to obtain a high-performance base film for the composite current collector, the base film thickness is 2-4.5 μm.

[0042] Preferably, the method for preparing the high-performance base film for the composite current collector comprises the following steps:

[0043] S1. Mix the PP masterbatch and the composite modified auxiliary particles in a mass ratio of 100:18, stir for 30 minutes, and then heat to 225° C. through a screw melt extrusion system to form a molten body, inject into a die head for extrusion after filtering, and cool to obtain a cast sheet;

[0044] S2, preheating the cast sheet to 110° C., and biaxially stretching the sheet at 160° C., with a longitudinal stretching ratio of 3 times and a transverse stretching ratio of 3.5 times, to obtain a stretched sheet;

[0045] S3, heat setting the stretched sheet at 170°C for 15 seconds, and then cooling to room temperature to obtain a crude product;

[0046] S4. Performing surface corona treatment on the crude product;

[0047] S5, winding, aging treatment: standing at 35°C for 2 days; cutting to obtain a high-performance base film for the composite current collector, the base film thickness is 4 μm.

[0048] The present invention also provides a high-performance base film for a composite current collector, which is prepared by the method as described above. The base film is used to prepare the composite current collector by a water electroplating copper process.

[0049] The beneficial effects of the present invention are:

[0050] The present invention provides a high-performance base film for a composite current collector and a preparation method thereof. The present invention can well solve the problem of poor copper adhesion of conventional PP base films, and can also significantly improve the flame retardant properties and tensile strength of the PP base film, which is conducive to promoting the large-scale application of PP materials in composite current collector base films.

[0051] In the present invention, the composite modified auxiliary particles can improve the adhesion of the PP base film, increase the interface bonding force between the PP base film and the metal conductive layer, and improve its flame retardant performance and tensile strength; in the present invention, wollastonite is modified by stearic acid, and the stearic acid on the surface of wollastonite can chemically react with the anhydride group on the PP-MAH to form a chemical bond at the interface between wollastonite and PP, thereby promoting the dispersion of wollastonite in PP and improving the reinforcing effect of wollastonite, and can improve the tensile strength and impact strength of the base film within a certain range;

[0052] In the present invention, the anhydride groups on the maleic anhydride grafted polypropylene PP-MAH can react chemically with the stearic acid on the surface of the modified wollastonite and the modified magnesium hydroxide to form chemical bonds, thereby promoting the uniform dispersion of the wollastonite and the magnesium hydroxide in the PP system, and can help the magnesium hydroxide to maintain a stable dispersion state in the system and avoid its surface migration;

[0053] In the present invention, acrylonitrile is grafted onto PP, which is an auxiliary particle precursor, and then an amination treatment is performed to obtain a composite modified auxiliary particle, thereby forming a large number of chelating segments with rich amine groups on PP. The amine groups on the chelating segments can chelate with metal ions to form coordination bonds, and have strong adsorption properties and strong binding force for metal ions. Therefore, in the process of water electroplating copper, copper ions can be efficiently and massively adsorbed onto the surface of the base film, and a strong binding force is formed between the base film and the base film, which can ultimately improve the efficiency and effect of copper plating, and enhance the interface bonding strength between the copper conductive layer and the base film. DETAILED DESCRIPTION

[0054] The present invention is further described in detail below in conjunction with embodiments so that those skilled in the art can implement the invention with reference to the description.

[0055] It should be understood that the terms such as “having”, “including” and “comprising” used herein do not exclude the existence or addition of one or more other elements or combinations thereof.

[0056] The test methods used in the following examples are conventional methods unless otherwise specified. The materials and reagents used in the following examples are all commercially available unless otherwise specified. In the following examples, if no specific conditions are specified, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not specified, are all conventional products that can be purchased commercially.

[0057] The present invention provides a high-performance base film for a composite current collector, and a preparation method thereof comprises the following steps:

[0058] S1. Mix the PP masterbatch and the composite modified auxiliary particles in a mass ratio of 100:5-23, stir for 15-60 minutes, and then heat to 200-240° C. through a screw melt extrusion system to form a molten body, inject into a die head for extrusion after filtering, and cool to obtain a cast sheet;

[0059] S2, preheating the cast sheet to 100-120°C, and biaxially stretching it at 150-175°C, with a longitudinal stretching ratio of 2-3.8 times and a transverse stretching ratio of 2.3-4 times to obtain a stretched sheet;

[0060] S3, heat setting the stretched sheet at 160-180° C. for 10-20 seconds, and then cooling to room temperature to obtain a crude product;

[0061] S4. Performing surface corona treatment on the crude product;

[0062] S5, winding, aging treatment: standing at 25-38°C for 1-3 days; cutting to obtain a high-performance base film for the composite current collector, the base film thickness is 2-4.5 μm.

[0063] The base film prepared by the invention is used for preparing a composite current collector through a water electroplating copper process.

[0064] In the present invention, the composite modified auxiliary particles are prepared by the following method:

[0065] 1) Preparation of modified wollastonite:

[0066] 1-1) adding 50-200 mg of wollastonite into 100-300 mL of anhydrous ethanol, and ultrasonically dispersing for 10-45 min to obtain a wollastonite dispersion;

[0067] 1-2) 1.25-5 mg of stearic acid is dissolved in 10-40 mL of ethanol, stirred for 2-15 min, the resulting mixture is added to the wollastonite dispersion, stirred for 5-30 min, then heated to 75-85 ° C, stirred at 500-1000 rpm for 30-90 min, cooled to room temperature, filtered, and the solid product is dried at 60-75 ° C for 8-16 h to obtain modified wollastonite.

[0068] 2) Preparation of modified magnesium hydroxide:

[0069] 2-1) adding 50-200 mg of magnesium hydroxide to 100-400 mL of anhydrous ethanol, and ultrasonically dispersing for 15-60 min to obtain a magnesium hydroxide dispersion;

[0070] 2-2) 0.75-3 mg of stearic acid and 0.65-2.5 mg of silane coupling agent KH-570 are added to 15-60 mL of ethanol, stirred for 5-30 min, and the resulting mixture is added to a magnesium hydroxide dispersion, ultrasonically dispersed for 15-60 min, then heated to 70-80 ° C, stirred at 300-800 rpm for 60-120 min, cooled to room temperature, filtered, and the solid product was dried at 60-70 ° C for 5-20 h to obtain modified magnesium hydroxide.

[0071] 3) Preparation of maleic anhydride grafted polypropylene PP-MAH:

[0072] PP (polypropylene) is dried at 70-85°C for 15-60 minutes, then mixed with MAH (maleic anhydride), DCP (diisopropyl peroxide), TPP (triphenyl phosphite), stirred for 5-30 minutes, then banburyed at 160-185°C for 5-20 minutes under continuous stirring, and cooled to room temperature to obtain maleic anhydride grafted polypropylene: PP-MAH;

[0073] Among them, the mass ratio of PP:MAH:DCP:TPP is 100:2.25-6.5:0.35-1.4:0.15-0.7.

[0074] 4) Preparation of auxiliary particle precursor:

[0075] PP-MAH, modified wollastonite and modified magnesium hydroxide are mixed, stirred at 90-105°C for 15-60 minutes, then added into a twin-screw extruder, extruded and granulated at 175-190°C to obtain an auxiliary granule precursor;

[0076] Wherein, the mass ratio of PP-MAH: modified wollastonite: modified magnesium hydroxide is 100: 4-16: 2.5-10.

[0077] 5) Preparation of composite modified auxiliary particles:

[0078] 5-1) Soak the auxiliary particle precursor in acetone for 4-12 hours, then rinse with deionized water, and dry at 50-70°C for 3-12 hours;

[0079] 5-2) Add acrylonitrile to N, N-dimethylacetamide solution to prepare a grafting monomer solution with a mass fraction of acrylonitrile of 10-20%; then add the auxiliary particle precursor to the grafting monomer solution at a mass ratio of acrylonitrile to auxiliary particle precursor of 1.3-2.4:1, seal and ultrasonically oscillate for 1.5-6 hours, then irradiate (EB irradiation source, ELV-8 electron accelerator), control the irradiation dose to 30-100KGy, filter after irradiation, soak the solid product with DMF for 0.5-2 hours, filter, wash the solid with ethanol, and then dry at 60-75°C for 3-12 hours to obtain grafted modified auxiliary particles;

[0080] 5-2) adding the grafted modified auxiliary particles, DETA and aluminum chloride into acetone and stirring evenly, reacting at 100-120° C. for 1.5-6 hours, cooling to room temperature after the reaction, filtering, washing the solid product with deionized water and ethanol in sequence, and then vacuum drying at 65-80° C. for 5-24 hours to obtain composite modified auxiliary particles;

[0081] Wherein, the mass ratio of grafted modified auxiliary particles: DETA: aluminum chloride is 100: 11.5-36: 0.5-2.

[0082] The present invention provides a high-performance PP base film for a composite current collector, which can effectively solve the problem of poor copper adhesion of conventional PP base films, and can also significantly improve the flame retardant properties and tensile strength of the PP base film, which is conducive to promoting the large-scale application of PP materials in composite current collector base films.

[0083] In the present invention, the composite modified auxiliary particles can improve the adhesion ability of the PP base film, enhance the interfacial bonding force between the PP base film and the metal conductive layer, and enhance its flame retardant properties and tensile strength. The composite modified auxiliary particles have multi-effect enhancement functions. The main mechanism thereof is described below in conjunction with its preparation method to facilitate the understanding of the present invention.

[0084] (1) In the present invention, wollastonite is first modified by stearic acid to prepare modified wollastonite; and magnesium hydroxide is composite-modified by stearic acid and a silane coupling agent to prepare modified magnesium hydroxide.

[0085] Wollastonite is a cheap, stable, and excellent filling material. Its filling in PP can play a heterogeneous nucleation role, accelerate the crystallization rate, and make the grains smaller, which can improve the modulus of the material to a certain extent. However, wollastonite is easy to agglomerate in PP resin, and the thermal stress cannot be relieved, resulting in more internal stress concentration areas, which will crack the impact performance of the material. In the present invention, the above problems can be improved by modifying wollastonite with stearic acid. The stearic acid on the surface of wollastonite can react chemically with the anhydride groups on PP-MAH, forming chemical bonds at the interface of wollastonite and PP, thereby promoting the dispersion of wollastonite in PP and improving the reinforcing effect of wollastonite, which can improve the tensile strength and impact strength of the base film within a certain range.

[0086] Magnesium hydroxide is a conventional inorganic flame retardant with excellent flame retardant properties, but it has the defects of being difficult to disperse evenly and easy to migrate on the surface in an organic system, which makes it difficult to fully exert its flame retardant properties and easily loses the mechanical strength of the organic system (such as when the addition amount is too large or agglomerates). In the present invention, by using stearic acid and a silane coupling agent to modify the surface of magnesium hydroxide, it can promote its uniform dispersion in the PP organic system, which can well solve the above problems.

[0087] (2) In the present invention, maleic anhydride grafted polypropylene PP-MAH is blended with modified wollastonite and modified magnesium hydroxide, and melt extruded to prepare an auxiliary particle precursor;

[0088] The anhydride groups on the maleic anhydride grafted polypropylene PP-MAH can react chemically with the stearic acid on the surface of the modified wollastonite and the modified magnesium hydroxide to form chemical bonds, thereby promoting the uniform dispersion of the wollastonite and the magnesium hydroxide in the PP system, and can help keep the magnesium hydroxide in a stable dispersed state in the system to avoid its surface migration.

[0089] (3) The present invention further grafts acrylonitrile onto the PP of the auxiliary particle precursor, and then performs an amination treatment to obtain a composite modified auxiliary particle, thereby forming a large number of chelating segments with rich amino groups on the PP. The amino groups on the chelating segments can chelate with metal ions to form coordination bonds, and have strong adsorption properties and strong binding force for metal ions. Therefore, during the water electroplating copper process, copper ions can be efficiently and massively adsorbed onto the surface of the base film, and a strong binding force is formed between the base film and the base film, which can ultimately improve the copper plating efficiency and effect, and enhance the interface bonding strength between the copper conductive layer and the base film.

[0090] (4) Finally, the present invention blends and extrude the composite modified auxiliary particles with the PP masterbatch. The composite modified auxiliary particles are a composite structure system with PP having a chelating chain segment as a carrier, and modified wollastonite and modified magnesium hydroxide as active substances. The loading effect of the composite modified auxiliary particles can promote the full compatibility of the active substances thereon with the PP masterbatch, and finally achieve uniform dispersion in the PP base film.

[0091] The above is the overall concept of the present invention, and detailed embodiments and comparative examples are provided below on the basis of the overall concept of the present invention to further illustrate the present invention.

[0092] The main sources of raw materials involved in the following examples and comparative examples are as follows:

[0093] Wollastonite, 1250 mesh, Jiangxi Huajietai Mineral Fiber Technology Co., Ltd.;

[0094] Magnesium hydroxide, average particle size 2 μm, Shanghai Qiren Chemical Co., Ltd.;

[0095] PP (polypropylene), brand M800E, Shanghai Petrochemical; MAH (maleic anhydride), Aozun Composite New Materials Co., Ltd.; DCP (diisopropyl peroxide), Shanghai Lingfeng Chemical Reagent Co., Ltd.; TPP (triphenyl phosphite TPP, Jiangsu Leien Environmental Protection Technology Co., Ltd.); AN (acrylonitrile), Shandong Chuangying Chemical Co., Ltd.; DETA (diethylenetriamine), Dow Chemical Co., Ltd.

[0096] The remaining raw materials are all commercially available conventional products.

[0097] Example 1

[0098] A high-performance base film for a composite current collector, the preparation method of which comprises the following steps:

[0099] S1. PP masterbatch (i.e. PP, grade M800E, Shanghai Petrochemical) and composite modified auxiliary particles were mixed in a mass ratio of 100:18, stirred for 30 minutes, and then heated to 225° C. through a screw melt extrusion system to form a molten body, which was injected into a die for extrusion after filtration and cooled to obtain a cast sheet;

[0100] S2, preheating the cast sheet to 110° C., and biaxially stretching the sheet at 160° C., with a longitudinal stretching ratio of 3 times and a transverse stretching ratio of 3.5 times, to obtain a stretched sheet;

[0101] S3, heat setting the stretched sheet at 170°C for 15 seconds, and then cooling to room temperature to obtain a crude product;

[0102] S4. Performing surface corona treatment on the crude product;

[0103] S5, winding, aging treatment: standing at 35°C for 2 days; cutting to obtain a high-performance base film for the composite current collector, the base film thickness is 4 μm.

[0104] In this embodiment, the composite modified auxiliary particles are prepared by the following method:

[0105] 1) Preparation of modified wollastonite:

[0106] 1-1) adding 100 mg of wollastonite into 200 mL of anhydrous ethanol and dispersing by ultrasonic for 20 min to obtain a wollastonite dispersion;

[0107] 1-2) 2.5 mg of stearic acid was dissolved in 20 mL of ethanol and stirred for 5 min. The resulting mixture was added to the wollastonite dispersion and stirred for 15 min. The mixture was then heated to 82° C. and stirred at 700 rpm for 60 min. The mixture was cooled to room temperature and filtered. The solid product was dried at 70° C. for 12 h to obtain modified wollastonite.

[0108] 2) Preparation of modified magnesium hydroxide:

[0109] 2-1) adding 100 mg of magnesium hydroxide into 200 mL of anhydrous ethanol and ultrasonically dispersing for 30 min to obtain a magnesium hydroxide dispersion;

[0110] 2-2) 1.5 mg of stearic acid and 1.3 mg of silane coupling agent KH-570 were added to 30 mL of ethanol and stirred for 10 min. The resulting mixture was added to the magnesium hydroxide dispersion and ultrasonically dispersed for 30 min. The mixture was then heated to 75 ° C. and stirred at 500 rpm for 90 min. The mixture was cooled to room temperature and filtered. The solid product was dried at 65 ° C. for 10 h to obtain modified magnesium hydroxide.

[0111] 3) Preparation of maleic anhydride grafted polypropylene PP-MAH:

[0112] The PP was dried at 80°C for 30 min, then mixed with MAH, DCP, and TPP, stirred for 15 min, and then banburying at 175°C for 15 min under continuous stirring, and cooled to room temperature to obtain maleic anhydride grafted polypropylene: PP-MAH;

[0113] Among them, the mass ratio of PP:MAH:DCP:TPP is 100:4.5:0.7:0.35.

[0114] 4) Preparation of auxiliary particle precursor:

[0115] PP-MAH, modified wollastonite and modified magnesium hydroxide were mixed, stirred at 95°C for 30 minutes, and then added into a twin-screw extruder, extruded and granulated at 185°C with a screw speed of 70 rpm to obtain an auxiliary particle precursor;

[0116] Among them, the mass ratio of PP-MAH: modified wollastonite: modified magnesium hydroxide is 100:9:5.

[0117] 5) Preparation of composite modified auxiliary particles:

[0118] 5-1) Soak the auxiliary particle precursor in acetone for 6 hours, then rinse with deionized water, and dry at 60°C for 8 hours;

[0119] 5-2) Add acrylonitrile to N, N-dimethylacetamide solution to prepare a grafted monomer solution with a mass fraction of 15% acrylonitrile; then add the auxiliary particle precursor to the grafted monomer solution at a mass ratio of 1.75:1 of acrylonitrile: auxiliary particle precursor, seal and ultrasonically oscillate for 3 hours, then irradiate, control the irradiation dose to 80KGy, filter after irradiation, soak the solid product with DMF for 1 hour, filter, wash the solid with ethanol, and then dry at 70°C for 6 hours to obtain grafted modified auxiliary particles;

[0120] 5-2) adding the grafted modified auxiliary particles, DETA and aluminum chloride into acetone and stirring evenly, reacting at 115° C. for 3 h, cooling to room temperature after the reaction, filtering, washing the solid product with deionized water and ethanol in sequence, and then vacuum drying at 70° C. for 10 h to obtain composite modified auxiliary particles;

[0121] Among them, the mass ratio of grafted modified auxiliary particles: DETA: aluminum chloride is 100:23:1.5.

[0122] Example 2

[0123] A high-performance base film for a composite current collector, the preparation method of which comprises the following steps:

[0124] S1. Mix the PP masterbatch and the composite modified auxiliary particles in a mass ratio of 100:16, stir for 30 minutes, and then heat to 225°C through a screw melt extrusion system to form a molten body, inject into a die head for extrusion after filtering, and cool to obtain a cast sheet;

[0125] S2, preheating the cast sheet to 110° C., and biaxially stretching the sheet at 160° C., with a longitudinal stretching ratio of 3 times and a transverse stretching ratio of 3.5 times, to obtain a stretched sheet;

[0126] S3, heat setting the stretched sheet at 170°C for 15 seconds, and then cooling to room temperature to obtain a crude product;

[0127] S4. Performing surface corona treatment on the crude product;

[0128] S5, winding, aging treatment: standing at 35°C for 2 days; cutting to obtain a high-performance base film for the composite current collector, the base film thickness is 4 μm.

[0129] In this embodiment, the composite modified auxiliary particles are prepared by the following method:

[0130] 1) Preparation of modified wollastonite:

[0131] 1-1) adding 100 mg of wollastonite into 200 mL of anhydrous ethanol and dispersing by ultrasonic for 20 min to obtain a wollastonite dispersion;

[0132] 1-2) 2.5 mg of stearic acid was dissolved in 20 mL of ethanol and stirred for 5 min. The resulting mixture was added to the wollastonite dispersion and stirred for 15 min. The mixture was then heated to 82° C. and stirred at 700 rpm for 60 min. The mixture was cooled to room temperature and filtered. The solid product was dried at 70° C. for 12 h to obtain modified wollastonite.

[0133] 2) Preparation of modified magnesium hydroxide:

[0134] 2-1) adding 100 mg of magnesium hydroxide into 200 mL of anhydrous ethanol and ultrasonically dispersing for 30 min to obtain a magnesium hydroxide dispersion;

[0135] 2-2) 1.5 mg of stearic acid and 1.3 mg of silane coupling agent KH-570 were added to 30 mL of ethanol and stirred for 10 min. The resulting mixture was added to the magnesium hydroxide dispersion and ultrasonically dispersed for 30 min. The mixture was then heated to 75 ° C. and stirred at 500 rpm for 90 min. The mixture was cooled to room temperature and filtered. The solid product was dried at 65 ° C. for 10 h to obtain modified magnesium hydroxide.

[0136] 3) Preparation of maleic anhydride grafted polypropylene PP-MAH:

[0137] The PP was dried at 80°C for 30 min, then mixed with MAH, DCP, and TPP, stirred for 15 min, and then banburying at 175°C for 15 min under continuous stirring, and cooled to room temperature to obtain maleic anhydride grafted polypropylene: PP-MAH;

[0138] Among them, the mass ratio of PP:MAH:DCP:TPP is 100:4.8:0.75:0.4.

[0139] 4) Preparation of auxiliary particle precursor:

[0140] PP-MAH, modified wollastonite and modified magnesium hydroxide were mixed, stirred at 95°C for 30 minutes, and then added into a twin-screw extruder, extruded and granulated at 185°C with a screw speed of 70 rpm to obtain an auxiliary particle precursor;

[0141] Among them, the mass ratio of PP-MAH: modified wollastonite: modified magnesium hydroxide is 100:9:5.

[0142] 5) Preparation of composite modified auxiliary particles:

[0143] 5-1) Soak the auxiliary particle precursor in acetone for 6 hours, then rinse with deionized water, and dry at 60°C for 8 hours;

[0144] 5-2) Add acrylonitrile to N, N-dimethylacetamide solution to prepare a grafted monomer solution with a mass fraction of 15% acrylonitrile; then add the auxiliary particle precursor to the grafted monomer solution at a mass ratio of 1.65:1 of acrylonitrile: auxiliary particle precursor, seal and ultrasonically oscillate for 3 hours, then irradiate, control the irradiation dose to 80KGy, filter after irradiation, soak the solid product with DMF for 1 hour, filter, wash the solid with ethanol, and then dry at 70°C for 6 hours to obtain grafted modified auxiliary particles;

[0145] 5-2) adding the grafted modified auxiliary particles, DETA and aluminum chloride into acetone and stirring evenly, reacting at 115° C. for 3 h, cooling to room temperature after the reaction, filtering, washing the solid product with deionized water and ethanol in sequence, and then vacuum drying at 70° C. for 10 h to obtain composite modified auxiliary particles;

[0146] Among them, the mass ratio of grafted modified auxiliary particles: DETA: aluminum chloride is 100:22:1.5.

[0147] Example 3

[0148] A high-performance base film for a composite current collector, the preparation method of which comprises the following steps:

[0149] S1, PP masterbatch and composite modified auxiliary particles were mixed in a mass ratio of 100:19.5, stirred for 30 minutes, and then heated to 225°C by a screw melt extrusion system to form a molten body, which was injected into a die for extrusion after filtering, and cooled to obtain a cast sheet;

[0150] S2, preheating the cast sheet to 110° C., and biaxially stretching the sheet at 160° C., with a longitudinal stretching ratio of 3 times and a transverse stretching ratio of 3.5 times, to obtain a stretched sheet;

[0151] S3, heat setting the stretched sheet at 170°C for 15 seconds, and then cooling to room temperature to obtain a crude product;

[0152] S4. Performing surface corona treatment on the crude product;

[0153] S5, winding, aging treatment: standing at 35°C for 2 days; cutting to obtain a high-performance base film for the composite current collector, the base film thickness is 4 μm.

[0154] In this embodiment, the composite modified auxiliary particles are prepared by the following method:

[0155] 1) Preparation of modified wollastonite:

[0156] 1-1) adding 100 mg of wollastonite into 200 mL of anhydrous ethanol and dispersing by ultrasonic for 20 min to obtain a wollastonite dispersion;

[0157] 1-2) 2.8 mg of stearic acid was dissolved in 20 mL of ethanol and stirred for 5 min. The resulting mixture was added to the wollastonite dispersion and stirred for 15 min. The mixture was then heated to 82° C. and stirred at 700 rpm for 60 min. The mixture was cooled to room temperature and filtered. The solid product was dried at 70° C. for 12 h to obtain modified wollastonite.

[0158] 2) Preparation of modified magnesium hydroxide:

[0159] 2-1) adding 100 mg of magnesium hydroxide into 200 mL of anhydrous ethanol and ultrasonically dispersing for 30 min to obtain a magnesium hydroxide dispersion;

[0160] 2-2) 1.7 mg of stearic acid and 1.4 mg of silane coupling agent KH-570 were added to 30 mL of ethanol and stirred for 10 min. The resulting mixture was added to the magnesium hydroxide dispersion and ultrasonically dispersed for 30 min. The mixture was then heated to 75 ° C. and stirred at 500 rpm for 90 min. The mixture was cooled to room temperature and filtered. The solid product was dried at 65 ° C. for 10 h to obtain modified magnesium hydroxide.

[0161] 3) Preparation of maleic anhydride grafted polypropylene PP-MAH:

[0162] The PP was dried at 80°C for 30 min, then mixed with MAH, DCP, and TPP, stirred for 15 min, and then banburying at 175°C for 15 min under continuous stirring, and cooled to room temperature to obtain maleic anhydride grafted polypropylene: PP-MAH;

[0163] Among them, the mass ratio of PP:MAH:DCP:TPP is 100:4.3:0.9:0.35.

[0164] 4) Preparation of auxiliary particle precursor:

[0165] PP-MAH, modified wollastonite and modified magnesium hydroxide were mixed, stirred at 95°C for 30 minutes, and then added into a twin-screw extruder, extruded and granulated at 185°C with a screw speed of 70 rpm to obtain an auxiliary particle precursor;

[0166] Among them, the mass ratio of PP-MAH: modified wollastonite: modified magnesium hydroxide is 100:9.5:5.

[0167] 5) Preparation of composite modified auxiliary particles:

[0168] 5-1) Soak the auxiliary particle precursor in acetone for 6 hours, then rinse with deionized water, and dry at 60°C for 8 hours;

[0169] 5-2) Add acrylonitrile to N, N-dimethylacetamide solution to prepare a grafted monomer solution with a mass fraction of 15% acrylonitrile; then add the auxiliary particle precursor to the grafted monomer solution at a mass ratio of 1.8:1 of acrylonitrile: auxiliary particle precursor, seal and ultrasonically oscillate for 3 hours, then irradiate, control the irradiation dose to 80KGy, filter after irradiation, soak the solid product with DMF for 1 hour, filter, wash the solid with ethanol, and then dry at 70°C for 6 hours to obtain grafted modified auxiliary particles;

[0170] 5-2) adding the grafted modified auxiliary particles, DETA and aluminum chloride into acetone and stirring evenly, reacting at 115° C. for 3 h, cooling to room temperature after the reaction, filtering, washing the solid product with deionized water and ethanol in sequence, and then vacuum drying at 70° C. for 10 h to obtain composite modified auxiliary particles;

[0171] Among them, the mass ratio of grafted modified auxiliary particles: DETA: aluminum chloride is 100:23:1.5.

[0172] Comparative Example 1

[0173] A high-performance base film for a composite current collector, the preparation method of which comprises the following steps:

[0174] S1. The PP masterbatch is heated to 225°C through a screw melt extrusion system to become a melt, which is then injected into a die for extrusion after filtration and cooled to obtain a cast sheet;

[0175] S2, preheating the cast sheet to 110° C., and biaxially stretching the sheet at 160° C., with a longitudinal stretching ratio of 3 times and a transverse stretching ratio of 3.5 times, to obtain a stretched sheet;

[0176] S3, heat setting the stretched sheet at 170°C for 15 seconds, and then cooling to room temperature to obtain a crude product;

[0177] S4. Performing surface corona treatment on the crude product;

[0178] S5, winding, aging treatment: standing at 35°C for 2 days; cutting to obtain a high-performance base film for the composite current collector, the base film thickness is 4 μm.

[0179] Comparative Example 2

[0180] This example is basically the same as Example 1, except for the preparation method of the composite modified auxiliary particles. In this example, the composite modified auxiliary particles are prepared by the following method:

[0181] 1) Preparation of maleic anhydride grafted polypropylene PP-MAH:

[0182] The PP was dried at 80°C for 30 min, then mixed with MAH, DCP, and TPP, stirred for 15 min, and then banburying at 175°C for 15 min under continuous stirring, and cooled to room temperature to obtain maleic anhydride grafted polypropylene: PP-MAH;

[0183] Among them, the mass ratio of PP:MAH:DCP:TPP is 100:4.5:0.7:0.35.

[0184] 2) Preparation of auxiliary particle precursor:

[0185] PP-MAH, wollastonite and magnesium hydroxide were mixed, stirred at 95°C for 30 minutes, then added into a twin-screw extruder, extruded and granulated at 185°C with a screw speed of 70 rpm to obtain an auxiliary particle precursor;

[0186] Among them, the mass ratio of PP-MAH: wollastonite: magnesium hydroxide is 100:9:5.

[0187] 3) Prepare the composite modified auxiliary particles in the same manner as in Example 1.

[0188] Comparative Example 3

[0189] This example is basically the same as Example 1, except that the only difference is the preparation method of the composite modified auxiliary particles. In this example, the composite modified auxiliary particles are prepared by the following method:

[0190] 1) preparing modified wollastonite, the same as in Example 1;

[0191] 2) preparing modified magnesium hydroxide, the same as in Example 1;

[0192] 3) Preparation of auxiliary particle precursor:

[0193] The PP was dried at 80°C for 30 minutes, and then the PP, modified wollastonite and modified magnesium hydroxide were mixed, stirred at 95°C for 30 minutes, and then added into a twin-screw extruder, extruded and granulated at 185°C with a screw speed of 70 rpm to obtain an auxiliary particle precursor;

[0194] Among them, the mass ratio of PP-MAH: modified wollastonite: modified magnesium hydroxide is 100:9:5.

[0195] 4) preparing composite modified auxiliary particles, the same as in Example 1;

[0196] Comparative Example 4

[0197] This example is basically the same as Example 1, except for the preparation method of the composite modified auxiliary particles. In this example, the composite modified auxiliary particles are prepared by the following method:

[0198] 1) preparing modified wollastonite, the same as in Example 1;

[0199] 2) preparing modified magnesium hydroxide, the same as in Example 1;

[0200] 3) preparing maleic anhydride grafted polypropylene PP-MAH, the same as in Example 1;

[0201] 4) Preparation of composite modified auxiliary particles:

[0202] PP was dried at 80°C for 30 minutes, and then PP, modified wollastonite and modified magnesium hydroxide were mixed; PP-MAH, modified wollastonite and modified magnesium hydroxide were mixed, stirred at 95°C for 30 minutes, and then added into a twin-screw extruder, extruded and granulated at 185°C, with a screw speed of 70 rpm, to obtain composite modified auxiliary particles;

[0203] Among them, the mass ratio of PP-MAH: modified wollastonite: modified magnesium hydroxide is 100:9:5.

[0204] Performance Testing

[0205] 1. Base film flame retardant performance test: The base film's limiting oxygen index is tested using standard JIS-K7201-3-2008 to evaluate its flame retardant performance. The larger the value, the better the flame retardant performance.

[0206] 2. A copper layer with a thickness of 1 μm was electroplated on the upper and lower surfaces of the base film using a water electroplating process to prepare a composite current collector. The specific process is: the base film is placed in an electroplating solution, electroplated at a temperature of 32°C and a current intensity of 2A, and air is continuously introduced into the electroplating solution during the electroplating process; the electroplating solution contains: 120 g / L copper sulfate, 95 g / L sulfuric acid and 50 mg / L hydrochloric acid. The composite current collector is then subjected to the following performance tests:

[0207] 2-1. Tensile strength and elongation at break: refer to the standard ASTM D882-12 "Standard test method for tensile properties of films and sheets", and use a universal tensile testing machine to test the tensile strength and elongation at break of the current collector;

[0208] 2-2. Square resistance: Use ST2253 digital four-probe tester to test the square resistance of the current collector;

[0209] 2-3. Adhesion test: Refer to the 100-grid test method in the standard "GB9286-2021" for the test: divide the test film into 250 small squares of 1x1mm, and then use 3M tape to tightly adhere the film, and then vertically peel off the tape, observe the detachment of the metal copper layer in each square, and calculate the 100-grid shedding rate / % to analyze the adhesion. The lower the shedding rate, the greater the adhesion.

[0210] Table 1

[0211]

[0212]

[0213] From the test results in Table 1, it can be seen that the base films prepared in Examples 1-3 have excellent flame retardant properties, and the limiting oxygen index is greatly improved compared with the pure PP film; the current collectors prepared from the base films of Examples 1-3 show higher tensile strength, and the adhesion between the base films and the copper layer is stronger;

[0214] In Comparative Example 1, since no composite modified auxiliary particles were added to the PP base film, the flame retardant properties of the base film were greatly reduced, and the comprehensive performance of the current collector was also significantly reduced; in Comparative Example 2, since wollastonite and magnesium hydroxide were not modified, their agglomeration in the PP system resulted in their respective reinforcing properties being unable to be fully exerted; in Comparative Example 3, maleic anhydride was not grafted onto polypropylene, which reduced the dispersion and stability of wollastonite and magnesium hydroxide in the PP system, resulting in a certain decrease in tensile strength and flame retardant properties; in Comparative Example 4, no chelating chain segments with amino groups were formed on PP, which greatly reduced the binding ability and binding strength of the PP base film with copper, and the test result showed a significant increase in the hundred-grid shedding rate. The increase in square resistance was due to the reduction in the density of the copper layer caused by the deterioration of the binding efficiency with copper ions.

[0215] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to specific details.

Claims

1. A method for preparing a high-performance base film for a composite current collector, characterized in that: The following steps are involved: S1, mixing the PP masterbatch with the composite modified auxiliary particles, melt-extruding, and cooling to obtain a cast sheet; S2, preheating the cast sheet and then biaxially stretching it to obtain a stretched sheet; S3, heat setting, cooling, and obtaining a crude product; S4. Performing surface corona treatment on the crude product; S5, winding, aging treatment, slitting, and obtaining a high-performance base film for a composite current collector; The composite modified auxiliary particles are prepared by the following method: 1) Modifying wollastonite with stearic acid to prepare modified wollastonite; 2) Using stearic acid and silane coupling agent to compositely modify magnesium hydroxide to prepare modified magnesium hydroxide; 3) Preparation of maleic anhydride grafted polypropylene: PP-MAH; 4) PP-MAH, modified wollastonite and modified magnesium hydroxide are blended and extruded by a twin-screw extruder to obtain an auxiliary particle precursor; 5) Grafting acrylonitrile onto PP as an auxiliary particle precursor, and then performing an amination treatment to obtain the composite modified auxiliary particle.

2. The method for preparing a high-performance base film for a composite current collector according to claim 1, characterized in that: Step 1) is as follows: 1-1) Add 50-200 mg of wollastonite into 100-300 mL of anhydrous ethanol and disperse by ultrasonic for 10-45 min to obtain a wollastonite dispersion; 1-2) Dissolve 1.25-5 mg of stearic acid in 10-40 mL of ethanol, stir for 2-15 min, add the resulting mixture to the wollastonite dispersion, stir for 5-30 min, then heat to 75-85 ° C, stir at 500-1000 rpm for 30-90 min, cool to room temperature, filter, and dry the solid product at 60-75 ° C for 8-16 h to obtain modified wollastonite.

3. The method for preparing a high-performance base film for a composite current collector according to claim 1, characterized in that: Step 2) is as follows: 2-1) Add 50-200 mg of magnesium hydroxide into 100-400 mL of anhydrous ethanol and disperse by ultrasonic for 15-60 min to obtain a magnesium hydroxide dispersion; 2-2) Add 0.75-3 mg of stearic acid and 0.65-2.5 mg of silane coupling agent KH-570 to 15-60 mL of ethanol, stir for 5-30 min, add the resulting mixture to the magnesium hydroxide dispersion, ultrasonically disperse for 15-60 min, then heat to 70-80 ° C, stir at 300-800 rpm for 60-120 min, cool to room temperature, filter, and dry the solid product at 60-70 ° C for 5-20 h to obtain modified magnesium hydroxide.

4. The method for preparing a high-performance base film for a composite current collector according to claim 1, characterized in that: Step 3) is as follows: The PP is dried at 70-85°C for 15-60 minutes, then mixed with MAH, DCP, and TPP, stirred for 5-30 minutes, and then banburyed at 160-185°C for 5-20 minutes under continuous stirring, and cooled to room temperature to obtain maleic anhydride grafted polypropylene: PP-MAH; Among them, the mass ratio of PP:MAH:DCP:TPP is 100:2.25-6.5:0.35-1.4:0.15-0.

7.

5. The method for preparing a high-performance base film for a composite current collector according to claim 1, characterized in that: Step 4) is as follows: PP-MAH, modified wollastonite and modified magnesium hydroxide are mixed, stirred at 90-105°C for 15-60 minutes, then added into a twin-screw extruder, extruded and granulated at 175-190°C to obtain an auxiliary granule precursor; Wherein, the mass ratio of PP-MAH: modified wollastonite: modified magnesium hydroxide is 100: 4-16: 2.5-10.

6. The method for preparing a high-performance base film for a composite current collector according to claim 1, characterized in that: Step 5) is as follows: 5-1) Soak the auxiliary particle precursor in acetone for 4-12 hours, then rinse with deionized water, and dry at 50-70℃ for 3-12 hours; 5-2) Add acrylonitrile to N, N-dimethylacetamide solution to prepare a grafting monomer solution with a mass fraction of acrylonitrile of 10-20%; then add the auxiliary particle precursor to the grafting monomer solution at a mass ratio of acrylonitrile to auxiliary particle precursor of 1.3-2.4:1, ultrasonically oscillate for 1.5-6 hours under sealing, and then irradiate, control the irradiation dose to 30-100KGy, filter after irradiation, soak the solid product with DMF for 0.5-2 hours, filter, wash the solid with ethanol, and then dry at 60-75°C for 3-12 hours to obtain grafted modified auxiliary particles; 5-2) Add the grafted modified auxiliary particles, DETA and aluminum chloride into acetone and stir evenly, react at 100-120°C for 1.5-6h, cool to room temperature after the reaction, filter, wash the solid product with deionized water and ethanol in turn, and then vacuum dry at 65-80°C for 5-24h to obtain composite modified auxiliary particles; Wherein, the mass ratio of grafted modified auxiliary particles: DETA: aluminum chloride is 100: 11.5-36: 0.5-2.

7. The method for preparing a high-performance base film for a composite current collector according to claim 1, characterized in that: The following steps are involved: S1. Mix the PP masterbatch and the composite modified auxiliary particles in a mass ratio of 100:5-23, stir for 15-60 minutes, and then heat to 200-240° C. through a screw melt extrusion system to form a molten body, inject into a die head for extrusion after filtering, and cool to obtain a cast sheet; S2, preheating the cast sheet to 100-120°C, and biaxially stretching it at 150-175°C, with a longitudinal stretching ratio of 2-3.8 times and a transverse stretching ratio of 2.3-4 times to obtain a stretched sheet; S3, heat setting the stretched sheet at 160-180° C. for 10-20 seconds, and then cooling to room temperature to obtain a crude product; S4. Performing surface corona treatment on the crude product; S5, winding, aging treatment: standing at 25-38°C for 1-3 days; cutting to obtain a high-performance base film for the composite current collector, the base film thickness is 2-4.5 μm.

8. The method for preparing a high-performance base film for a composite current collector according to claim 7, characterized in that: The following steps are involved: S1. Mix the PP masterbatch and the composite modified auxiliary particles in a mass ratio of 100:18, stir for 30 minutes, and then heat to 225° C. through a screw melt extrusion system to form a molten body, inject into a die head for extrusion after filtering, and cool to obtain a cast sheet; S2, preheating the cast sheet to 110° C., and biaxially stretching the sheet at 160° C., with a longitudinal stretching ratio of 3 times and a transverse stretching ratio of 3.5 times, to obtain a stretched sheet; S3, heat setting the stretched sheet at 170°C for 15 seconds, and then cooling to room temperature to obtain a crude product; S4. Performing surface corona treatment on the crude product; S5, winding, aging treatment: standing at 35°C for 2 days; cutting to obtain a high-performance base film for the composite current collector, the base film thickness is 4 μm.

9. A high-performance base film for a composite current collector, characterized in that: It is prepared by the method described in any one of claims 1 to 8, and the base film is used to prepare a composite current collector through a water electroplating copper process.

Citation Information

Patent Citations

  • Ultrathin polypropylene film as well as preparation method and application thereof

    CN117087283A

Cited By

  • Dynamic self-repairing degradation-resistant composite current collector BOPET film and preparation method thereof

    CN120757831A

  • Dynamic self-healing degradation-resistant composite current collector bopet film and method of making

    CN120757831B

  • Preparation method of composite current collector base film based on flame-retardant anti-aging modified PP (polypropylene) and composite current collector

    CN121083961A

  • A method for preparing a composite current collector base film based on flame-retardant and aging-resistant modified PP and the composite current collector

    CN121083961B

  • High-bonding-strength flame-retardant composite current collector base film and preparation method thereof

    CN121226899A